(untitled) (Development Engineering Conferences Center Articles Database, 2026)
Maintaining and improving soil fertility is one of the main foundations of sustainable agriculture, which is facing serious problems today. Soil fertility, as the foundation of sustainable agricultural production and global food security, has become one of the most important scientific and management challenges in recent decades. Factors such as the decline in organic matter (which in many arid regions reaches below 1%), increasing salinity, and nutrient deficiencies due to monocultures, improper irrigation, and excessive use of chemical fertilizers have reduced agricultural land productivity by 20 to 50%, and these issues, especially in countries like Iran, both increase food insecurity and exacerbate environmental damage from climate change. Intensified exploitation of soil resources, climate change, physical erosion, disruption of the balance of nutrients, loss of microbial biodiversity, and unbalanced use of chemical inputs are among the key factors weakening soil health and reducing the efficiency of agricultural systems. The main challenges include the reduction of beneficial microbial activity due to the lack of soil organic carbon, wind and water erosion and nutrient loss. Soil degradation through wind and water erosion, severe reduction of organic matter, nutrient deficiency or imbalance, salinity and alkalinity, soil compaction, acidification, heavy metal contamination and pesticide residues, as well as climate change, seriously threaten the productive capacity of agricultural soils in many regions of the world, especially in developing countries. This article comprehensively reviews the main challenges of maintaining soil fertility within the framework of sustainable agriculture and proposes scientific evidence-based solutions. In this regard, effective solutions include: (1) integrated management with the incorporation of biofertilizers (such as rhizobia and mycorrhiza), plant residues increase the efficiency of nutrient uptake by 25-40%; (2) no-till and cover crops to increase carbon storage and soil strength; (3) use of biochar to adjust pH and retain carbon; and (4) crop rotation to improve biodiversity and pest control. (5) Integrated soil fertility management, including the intelligent combination of organic resources (compost, vermicompost, animal manure, crop residues, biochar) with targeted mineral fertilizers, along with conservation agriculture principles (minimum tillage, permanent soil cover, crop rotation and biodiversity, intercropping and cover crops), has shown much higher effectiveness in restoring soil physical, chemical, and biological properties. The role of soil microbiomes and complex microbial interactions in increasing nutrient availability, improving soil structure, reducing biotic and abiotic stresses, and strengthening the resilience of agricultural ecosystems has been emphasized as one of the emerging axes of sustainable agriculture. In the meantime, the bio-circular economy approach and recycling of agricultural organic waste can provide an effective path to reduce dependence on chemical inputs and improve long-term soil quality. The issues discussed will transform agricultural policies and reduce dependence on external inputs. The findings emphasize that achieving sustainable agriculture requires a shift from a consumerist paradigm to a soil ecosystem-based management; an approach that not only ensures food production, but also preserves and enhances soil ecosystem services (carbon storage, regulation of water and nutrient cycling, and biodiversity conservation). The results show that the reduction of soil organic carbon stocks and disruption of biological-biogeochemical cycles of nutrients play a pivotal role in the decline of physical, chemical, and biological quality of soils, and this trend can severely threaten the sustainability of production and the resilience of agricultural ecosystems. Future research should focus on smart soil sensors, economic issues for farmers. This review provides practical guidance for researchers and managers to maintain soil health for future generations through multilateral collaborations at the global community level.